Crisis periods of the Turkish tourism in 1990’s. - Kuzucu, Pelin (My University, 2002)
Crisis periods of the Turkish Tourism in 1990's konulu tez, iki ana bölümden oluşmaktadır. Literatür araştırmasının anlatıldığı ilk bölümde turizm ve kriz tanımları ikinci olarak da kriz yönetimi yer almaktadır. 1990'lı yıllarda yer alan Türk Turizmi Kriz dönemleri ile ilgili kişilerin görüşlerine ulaşabilmek için 150 anketin kullanıldığı saha araştırması yapılmıştır. Kriz dönemlerinin nedenleri anketi cevaplayan kişilerin görüşlerine göre oluşturulmuştur. Bu bölümde kriz sinyalleri, kriz tanımları, kriz öncesi ve sonrası yapılabilecekler, krizden etkilenen bölümler ve gerekli pazarlama faaliyetleri ele alınmıştır. Yukarıda sayılan bulgulara ilave olarak literatür araştırmasında yer alan turizm ve kriz tanımları saha araştırması sonuçları ne karşılaştırılmıştır. Son bölümde ise, öneri tablosu ve tezin genel sonuç bölümü yer almaktadır.

The thesis Crisis Periods of the Turkish Tourism in 1990's consists of two major parts. In the first part a literature survey puts forward the definitions of tourism and crisis. Next crisis management is discussed. A field research with a formal questionnaire, distributed to 150 people tries to put forward what and how people perceive the crisis periods of Turkish Tourism in 1990's. The reasons of crisis based on participants' perceptions are tried to be figured out. This included in detail the signals and the identification of what is called crisis, what can be done before and after, the crisis affected departments and the necessary marketing activities specifically promotional ones in crisis. In addition to these the findings from 150 questionnaires about definition of tourism and crisis are matched with literature definitions. The final part in conclusion covers the recommendations table and there is a final summary and conclusion section of the whole thesis.
Keywords: Kriz Yönetimi; Turizm-Türkiye